“The Kindness of Strangers:” The Influence of Social Media on the Construction of Factitious Disorder Imposed on Another - Langer, Rosanna (International Journal of Criminology and Sociology, 2022)
Factitious Disorder Imposed on Another (FDIA), termed a psychiatric “Factitious disorder by proxy”, compels individuals to solicit unnecessary medical interventions or commit medical abuses on another, almost always a child in their care. A recent phenomenon is that of individuals with FDIA using social media such as blogs and online support groups to perpetuate such abuse, while garnering sympathy from others who access these sites. Through an examination of several recent high profile FDIA by Internet cases and using the concept of “neo-tribes’ to identify the virtual communities of interest that form around these cases, new dimensions of FDIA appear. Fabrication of medical and social histories is facilitated and consolidated in the virtual sphere and readily enhanced through imagery and careful documentation. Betrayed communities experience exploitation and fraud. However, child neglect and child endangerment remain of concern, and identifying and investigating such claims across physical jurisdictions remain significant challenges for law enforcement.